KONSERVASI DAN PENGOLAHAN HIJAUAN PAKAN UNTUK PETERNAKAN BERKELANJUTAN - Witariadi, N.M; Roni, N.G.K.; Lindawati, S.A.; Kusumawati, N.N.C.; Siti, N.W. (Buletin Udayana Mengabdi; Vol 22 No 4 (2023): Buletin Udayana MengabdiDO - 10.24843/BUM.2023.v22.i04.p04, 2023)
This service aims to introduce superior forage types and create demonstration plots of superior forage plants, techniques for processing forage feeds and processing livestock waste. The method used in this service activity were interviews with farmers to find information about obstacles in procuring forage, counseling, making demonstration plots of superior forage and the practice of processing forage feed and livestock waste. The data obtained were analyzed descriptively to provide input on the problems faced by farmers. The results of this service activity were the realization of demonstration plots as superior forage centers, transfer of appropriate technology for processing forage into animal feed such as silage and fermented feed and processing livestock waste into organic fertilizer. It can be concluded from this activity the realization of demonstration plots as a center for superior forage seeds, processing forage and livestock waste with appropriate technology to increase the income of farmers. Keywords: demoplot, fermented, silase, fertilizer